2014
DOI: 10.1175/jas-d-13-0305.1
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Aerosol Impacts on Clouds and Precipitation Development in a Large Winter Cyclone

Abstract: Aerosols influence cloud and precipitation development in complex ways due to myriad feedbacks at a variety of scales from individual clouds through entire storm systems. This paper describes the implementation, testing, and results of a newly modified bulk microphysical parameterization with explicit cloud droplet nucleation and ice activation by aerosols. Idealized tests and a high-resolution, convection-permitting, continental-scale, 72-h simulation with five sensitivity experiments showed that increased ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
464
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 600 publications
(480 citation statements)
references
References 78 publications
13
464
2
1
Order By: Relevance
“…Studies of summertime convective precipitation in Germany found that increased aerosol concentrations had a strong effect on cloud microphysical (and therefore radiative) properties but that the combined effects of microphysical and dynamical processes resulted in relatively little effect on surface precipitation (Seifert et al, 2012). This is similar to the findings of Thompson and Eidhammer (2014) in idealised and continental-scale simulations.…”
Section: Introductionsupporting
confidence: 69%
“…Studies of summertime convective precipitation in Germany found that increased aerosol concentrations had a strong effect on cloud microphysical (and therefore radiative) properties but that the combined effects of microphysical and dynamical processes resulted in relatively little effect on surface precipitation (Seifert et al, 2012). This is similar to the findings of Thompson and Eidhammer (2014) in idealised and continental-scale simulations.…”
Section: Introductionsupporting
confidence: 69%
“…The main physics packages used in our WRF simulation are the Thompson aerosol-aware microphysics (Thompson and Eidhammer 2014), the Yonsei University (YSU) planetary boundary layer scheme (Hong et al 2006), the Rapid Radiative Transfer Model (RRTMG) (Iacono et al 2008), and the improved Noah-MP land surface model (Niu et al 2011). Additionally, an upgraded lake water temperature treatment is implemented and spectral nudging (von Storch et al 2000;Miguez-Macho et al 2004) of temperature, horizontal wind speed, and geopotential height is applied.…”
Section: Model Setup and Observational Datamentioning
confidence: 99%
“…the synoptic-scale atmospheric processes and much smallerscale cloud microphysical processes play a role in regulating the cyclone life cycle (Naud et al, 2016(Naud et al, , 2017Grandey et al, 2013;Deng, 2015, 2016;Thompson and Eidhammer, 2014;Igel et al, 2013;Zhang et al, 2007).…”
Section: T Mccoy Et Al: Aerosol Midlatitude Cyclone Indirect Effmentioning
confidence: 99%